Beyond Sex: Human Monkeypox Virus is an Emerging Threat to Marginalized Populations. (17th October 2022) - Barocas, Joshua A; Strathdee, Steffanie A
Abstract: The human version of the monkeypox virus (MPXV) is establishing itself to various degrees across the globe. While substantial attention has been focused on sexual risk, particularly among men who have sex with men, other populations are vulnerable to this virus. In particular, people experiencing homelessness and those with substance use disorders are vulnerable to MPXV. Overcrowded and unsanitary shelter conditions and city policies that force the relocation of people experiencing homelessness provide ample opportunity for the virus to flourish in this population. Furthermore, people with substance use disorders, specifically those who inject drugs, are at increased risk due to lack of access to sterile injection equipment. Herein, we present a spectrum of structural determinants underpinning increased risks in these populations and recommendations that could help mitigate the spread.